Finding Dory [videorecording (DVD)] - Stanton, Andrew (Distributed by Buena Vista Home Entertainment, 2016)
When Dory, the forgetful blue tang, suddenly remembers she has a family who may be looking for her, she, Marlin, and Nemo take off on a life-changing quest to find them, with help from Hank, a cantankerous octopus; Bailey, a beluga whale who's convinced his biological sonar skills are on the fritz; and Destiny, a nearsighted whale shark! Dive into the movie overflowing with unforgettable characters, dazzling animation, and gallons of fun!